Analisis Pengaruh Investasi Penanaman Modal Asing (PMA), Penanaman Modal Dalam Negeri (PMDN), Belanja Modal, dan Tenaga Kerja Terhadap Produk Domestik Regional Bruto di Kabupaten/Kota Provinsi NTB Tahun 2018-2022 - Adzin, M. Adzin Sadid; Hailuddin, Hailuddin; Wijimulawiani, Baiq Saripta (Postgraduate, University of Mataram, 2024)
This study aims to analyze the effect of foreign investment, domestic investment, local government capital expenditure, and labor on district/city GRDP in NTB Province in 2018-2022, and This study will also analyze which variables have the highest effect on the GRDP value. This study is a study that uses quantitative descriptive methods using data panel data analysis tools using EViews software 10. The results of this study indicate that foreign investment variables and domestic investment variables partially have a positive and significant effect on the GRDP variable, while the capital expenditure variable and labor variables have a positive but not significant influence. As for simultaneously the independent variables of foreign investment, domestic investment, capital expenditure, and labor simultaneously have a significant effect and for the highest variables on GRDP is a domestic investment variables.